2015
DOI: 10.5114/pg.2015.49684
|View full text |Cite
|
Sign up to set email alerts
|

Current management of anal fistulas in Crohn’s disease

Abstract: Anal fistulas occurring in Crohn's disease (CD) comprise a risk factor of severe course of inflammation. They are frequently intractable due to various factors such as penetration of the anal canal or rectal wall, impaired wound healing, and immunosuppression, among others. Anal fistulas typical to CD develop from fissures or ulcers of the anal canal or rectum. Accurate identification of the type of fistula, such as low and simple or high and complex, is crucial for prognosis as well as for the choice of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, a recent randomised-control trial (RCT) reported an association between supplementation, vitamin D receptor genotype, and risk of colorectal adenoma, supporting the premise that the beneficial effect may be causal [ 3 ]. Meanwhile, vitamin D-related genetic variation has been shown to influence the association between 25-OHD level and CRC survival [ 4 6 ], with a recent meta-analysis of RCT data strongly supporting a causal effect for vitamin D supplementation on CRC mortality [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent randomised-control trial (RCT) reported an association between supplementation, vitamin D receptor genotype, and risk of colorectal adenoma, supporting the premise that the beneficial effect may be causal [ 3 ]. Meanwhile, vitamin D-related genetic variation has been shown to influence the association between 25-OHD level and CRC survival [ 4 6 ], with a recent meta-analysis of RCT data strongly supporting a causal effect for vitamin D supplementation on CRC mortality [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sphincter-saving operations should be preceded by prolonged drainage with a noncutting seton until inflammation within the fistulous track recedes [26]. Cutting setons are not recommended due to the risk of damage to the sphincter or deformation of the anus [25]. In our study, the rabbit fistulas are healing at the last time after noncutting setons, but the anal deformation is serious, and fistula has a long healing time with scar and inflammation left.…”
Section: Discussionmentioning
confidence: 74%
“…Prolonged placement of noncutting setons remains a “gold standard” in the palliative treatment of fistulas [25]. Sphincter-saving operations should be preceded by prolonged drainage with a noncutting seton until inflammation within the fistulous track recedes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the anatomical factors causing recurrent disease, several other comorbidities increase the risk of anal fistula recurrence. These factors include anal cancer [22], Crohn’s disease [23], diabetes [24], smoking [25], and an immunosuppressed state like HIV [26].…”
Section: Reviewmentioning
confidence: 99%